APLIKASI BREAK EVEN POINT PADA SISTEM OPERASIONAL KAPAL MOTOR PENYEBERANGAN RODITHA PT. ASDP INDONESIA FERRY (PERSERO) CABANG LEMBAR - Wijana, Made; Triadi, A.A. ALit; Febriandi, Firza (Dinamika Teknik Mesin: Jurnal Keilmuan dan Terapan Teknik Mesin, 2014)
This study is intended to analyze the feasibility operation KMP Roditha which owned by PT. ASDP Indonesia Ferry (Limited). Location of research in the trajectory Sheet - Padang Bai, was used the Break Even Point. Collecting a range of cost of KMP Rodita, therefore was known the operating costs, maintenance costs and income from the sale of tickets while one year. Stepsare used in this research is the analysis of quantitative data, where i would collect the data required in relation to the matter to be investigated, so that research results can be more reliable and credible. The results of this study indicate that KMP Roditha income in 2010 was Rp. 12,007,178,916, of a total of 504 trips. Break Even Point in 2010 occurred in the 5th month on 213 trips, so that KMP Roditha feasible to operate.